Mitochondrial dysfunction in cardiovascular disease: investigating therapeutic approaches to enhance patient outcomes - Omar Elsaka (MGM Journal of Medical Sciences)
Mitochondria, the energy-generating organelles, undergo continuous biosynthesis, fission, fusion, and degradation cycles to maintain structural integrity. While mitochondria in the adult heart are relatively static, their structural modifications, governed by mitochondrial morphology, are crucial for energy production, organelle shape, and stress adaptation. Mitochondrial fusion is mediated by proteins such as Mitofusin 1 (Mfn1), Mitofusin 2 (Mfn2), and Optic Atrophy 1 (Opa1), which interact with the endoplasmic reticulum, enhance mitophagy, remodel cristae, and regulate apoptosis. In contrast, fission, driven by proteins like dynamin-related protein 1 (Drp1), fission 1 (Fis1), mitochondrial fission factor (Mff), and mitochondrial dynamics protein 49/51 (MiD49/51), facilitates the elimination of damaged mitochondria and supports cell division. Dysregulated mitochondrial dynamics contribute to various cardiac conditions, including cardiac hypertrophy, heart failure, and ischemia/reperfusion injury. Also, mitochondrial dysfunction and oxidative stress are implicated in atherosclerosis, hypertension, and pulmonary hypertension. Modulating mitochondrial dynamics presents a promising therapeutic approach for cardiac disorders. This study explores mitochondrial morphology in heart disease, highlighting key regulatory genes involved in mitochondrial dynamics and their potential as therapeutic targets.